1992
DOI: 10.1002/bit.260400806
|View full text |Cite
|
Sign up to set email alerts
|

Advanced control of glutathione fermentation process

Abstract: A study was performed to understand the fermentation process for production of glutathione fermentation (GSH) with an improved strain of baker's yeast. Simultaneous utilization of sugar and ethanol has been found to be a key factor in the industrial process to produce GSH using Saccharomyces cerevisiae KY6186. Based on this observation, the optimal sugar feed profile for the fed-batch operation has been determined. A feedforward/feedback control system was developed to regulate the sugar feed rate so as to max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 9 publications
0
28
0
Order By: Relevance
“…Further development of DCU capabilities lead to the expansion and the practical implementation of advanced fed-batch control techniques 4,5 such as adaptive control, soft sensoring (process models, artificial neural networks (ANN), principal component analysis (PCA)), intelligent control (fuzzy logic, ANN, hybrid models), and model predictive control (MPC) 6 introduced for pilot-scale and industrial applications 7,8,9 . On the other hand, these systems are not widely accessible due to their specialized and non-commercial use, whether developed for the research laboratory or the biotech company.…”
Section: Model Predictive Feeding Rate Control In Conventional and Simentioning
confidence: 99%
See 1 more Smart Citation
“…Further development of DCU capabilities lead to the expansion and the practical implementation of advanced fed-batch control techniques 4,5 such as adaptive control, soft sensoring (process models, artificial neural networks (ANN), principal component analysis (PCA)), intelligent control (fuzzy logic, ANN, hybrid models), and model predictive control (MPC) 6 introduced for pilot-scale and industrial applications 7,8,9 . On the other hand, these systems are not widely accessible due to their specialized and non-commercial use, whether developed for the research laboratory or the biotech company.…”
Section: Model Predictive Feeding Rate Control In Conventional and Simentioning
confidence: 99%
“…New Brunswick/Eppendorf (USA) presented feed control based on the on-line dissolved CO 2 sensor data 10 . The YEWMAC Line Computer System (Yokogawa Electric Corporation, Japan) at the beginning of the 1990's was used for model predictive feeding rate control in the glutathione fermentation to compensate deviation from preset (modeled) ethanol concentration 7 . MPC has an advantage of relatively easier implementation possibilities as compared to ANN or fuzzy logic-based control.…”
Section: Model Predictive Feeding Rate Control In Conventional and Simentioning
confidence: 99%
“…The increase of biomass and GSH after the sugar depletion in this study could also be related to the Crabtree effect, by which the respiratory enzymes were inhibited and ethanol was formed when the substrate concentration was above a critical value. In Sakato's report (Sakato and Tanaka 1992), it was shown that the simultaneous utilization of sugar and ethanol has been a key factors in the industrial process to produce GSH and no further increase in GSH was observed after ethanol was consumed in the medium. According to Wen et al (2006), ethanol concentration in the medium had a significant effect on GSH content in the fed-batch culture.…”
Section: Batch and Fed Batch Cultivation In Bioreactormentioning
confidence: 99%
“…A study on the effect of dissolved oxygen (DO) on CoQ10 production showed poor aeration conditions in A. tumefaciens [18] and a lower DO concentration in P. denitrificans [13] to favor CoQ10 production. Sakato et al [19] found CoQ10 production to be enhanced under microaerobic dark cultivation of Rhodopseudomonas sphaeroids. Choi et al [20] observed a four-fold increase of the specific CoQ10 content of A. tumefaciens on decreasing the DO concentration from 20 to 5 %.…”
Section: Introductionmentioning
confidence: 98%